2004
DOI: 10.1111/j.1469-8137.2004.01200.x
|View full text |Cite
|
Sign up to set email alerts
|

Is variation in susceptibility to Phytophthora ramorum correlated with population genetic structure in coast live oak (Quercus agrifolia)?

Abstract: Summary• California coastal woodlands are suffering severe disease and mortality as a result of infection from Phytophthora ramorum . Quercus agrifolia is one of the major woodland species at risk. This study investigated within-and among-population variation in host susceptibility to inoculation with P. ramorum and compared this with population genetic structure using molecular markers.• Susceptibility was assessed using a branch-cutting inoculation test. Trees were selected from seven natural populations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 36 publications
10
54
0
Order By: Relevance
“…Most of this variability may be explained by age of the infestation, by the amount of bay laurel intermixed with oaks (30,71,78,82), and by the number of other tree species present, with a higher diversity of species leading to lower overall infection rates (53). Additionally, intraspecific variability in oaks' susceptibility to P. ramorum has been observed in inoculation studies performed on detached branches of coast live oaks (32,33). Because these experiments were performed on excised plant parts of wild trees of unknown parentage, it has been impossible to determine whether the observed variation was genetically or environmentally determined, but it seems reasonable that both mechanisms may play a part.…”
Section: Ecology and Impacts Of Sod In California Forestsmentioning
confidence: 99%
“…Most of this variability may be explained by age of the infestation, by the amount of bay laurel intermixed with oaks (30,71,78,82), and by the number of other tree species present, with a higher diversity of species leading to lower overall infection rates (53). Additionally, intraspecific variability in oaks' susceptibility to P. ramorum has been observed in inoculation studies performed on detached branches of coast live oaks (32,33). Because these experiments were performed on excised plant parts of wild trees of unknown parentage, it has been impossible to determine whether the observed variation was genetically or environmentally determined, but it seems reasonable that both mechanisms may play a part.…”
Section: Ecology and Impacts Of Sod In California Forestsmentioning
confidence: 99%
“…The efficacy of these two chemical treatments was tested at 6, 12 and 18 months post-treatment by inoculating 10 cut branches per tree with P. ramorum as described in Dodd et al (2005). Terminal branches (0.8 to 1.2 millimeters diameter) were cut, immediately placed in water and transported to the UC Berkeley greenhouse.…”
Section: Longevity and Efficacy Studiesmentioning
confidence: 99%
“…In the same study, Dodd et al (2008) report a genetic component in the size of lesions to coast live oaks caused by P. ramorum (already hinted at in a previous study, not considered in the RAPRA report, Dodd et al (2005)). Although for P. ramorum in Europe and America there has not been hostpathogen co-evolution, there is still likely to be intraspecific genetic variation in susceptibility of the various host species (Nettel et al, 2009).…”
Section: Jung Et Al (2009) Write That Up To 2007 "Stem Infections Hamentioning
confidence: 69%
“…This study confirms the previously reported (in Mascheretti et al, 2008 already cited in the RAPRA report) spatial genetic autocorrelation profile with an increase in relatedness from a few hundred metres to about one km, which could be related to wind-dispersal, but also to artificial movements of the pathogen. Dodd et al (2008) report a genetic component in the size of lesions to coast live oaks caused by P. ramorum (already hinted at in a previous study, not considered in the RAPRA report (Dodd et al, 2005)). Although for P. ramorum in Europe and America there has not been host-pathogen coevolution, there is still likely to be intraspecific genetic variation in susceptibility of the various host species (Nettel et al, 2009).…”
Section: Options To Reduce Likelihood Of Spreadmentioning
confidence: 73%
See 1 more Smart Citation